THE POTENTIAL OF SAGO WASTE AS ANIMAL FEED IN THE DOA JAYA ABADI BUSINESS GROUP, MANOKWARI WEST PAPUA - Andoyo Supriyantono; Sri Hartini; Sientje D. Rumetor; Trisiwi W. Widayati; Elfira K. Suawa; Lukas Y. Sonbait; Noveling Inriani; Johanes Bosco Rengil (Jurnal Abdisci, 2024)
The sago dregs produced by the Doa Jaya Abadi Business Group are abundant and not used by farmers in the area. The business group engages in sago processing and packaged sago production. The Papua University Postgraduate Service Team visited the business group to find out the potential of the sago waste produced. A total of 20 lecturers and postgraduate students took to the field to carry out community service activities. Community service activities begin with communication between the postgraduate director and the Doa Jaya Abadi Business Group chairman. The livestock sector group assessed the potential of sago waste using survey methods and interviews with the head of the Doa Jaya Abadi business group. The community service results revealed the presence of sago worms in the sago waste surrounding the business group. In addition, fermentation can transform sago waste into animal feed.